Anatomical aspects in carrying of the practice classes «Devitalized pulpitis therapy». - Dmitrieva, E. A. (Морфологія / Morphologia / Morfologìâ, 2016)
The paper presents the main methodological aspects of the practice session with students on devitalized pulpitis therapy. It focuses on the necessity of thorough analysis of dental pulp inflammation, obligation of correct diagnosing of dental disease by symptoms as well as compliance with phased pulpotomy (pulp amputation) and pulpectomy (pulp extirpation).